Formulation of Bagelen With Mung Bean Flour Substitution as An Alternative Snack for Obesity - Khoiriyah, Nur; Wardiyanto, Yayan; Hadi, Risa; Harun; Fajrin Kurniawan, Fakhry; Suharto, Taufik Hidayat; Nur Sa'adah, Azizah; Saputra, Ade Fonny (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2026)
Obesity remains a nutritional problem in Indonesia. Diet therapy for obesity can be achieved through a high-fiber diet. One potential source of fiber is mung bean flour. Bagelen products with mung bean flour substitution have the potential to be developed into high-fiber products for obesity. The purpose of this study was to analyze the sensory properties and nutritional content of Bagelen formulations with mung bean flour substitution. This study used a completely randomized experimental Design conducted from August to November 2025. Product development and organoleptic testing were carried out in the nutrition laboratory, Universitas Muhammadiyah Cirebon. There were three Bagelen formulation treatments with different ratios of wheat flour to mung bean flour, including F1 (80:20), F2 (70:30), and F3 (60:40). The variables analyzed included organoleptic properties (30 panelists) and nutritional content (moisture, ash, protein, fat, carbohydrate, crude fiber, and energy). Data was analyzed using the ANOVA and Kruskal-Wallis tests. The results showed that mung bean flour substitution significantly affected hedonic organoleptic characteristics, including color, aroma, taste, texture, aftertaste, and overall acceptability (p<0.05). F1 is a selected formula with a nutritional content of 418.70 kcal of total energy, 4.67 kcal of water, 1.38 kcal of ash, 15.64 g of fat, 8.36 g of protein, 62.71 g of carbohydrates, and 7.23 g of fiber per 100 g. F1 also qualifies as a high-fiber food product. A Bagelen made with a mung bean flour substitute has the potential to be a healthy, high-fiber snack alternative for obese individuals.